Analisis Pengaruh Pelaksanaan Good Corporate Governance Terhadap Return Saham (Studi Kasus Pada Perusahaan Indeks KOMPAS100 yang Terdaftar di Bursa Efek Indonesia Tahun 2011-2015) - B31112017, WINA (Jurnal Manajemen Update, 2016)
This study aims to determine the effect of the Board of Commissioners (Commissioner), the Audit Committee (the Committee), CEO Duality (CEO), Institutional Ownership (Int) and Size Growth (Growth) either partially or simultaneously to Return Stock Companies Index Kompas 100 registered Indonesia stock exchange. The sample in this study were obtained by using purposive sampling techniques, thus obtained 33 samples of the study period 2011-2015. Data analysis techniques used in this research is multiple regression analysis using SPSS 16.0. The results showed that the Board of Commissioners and significant negative effect on the Stock Return. The Audit Committee and no significant negative effect on the Stock Return. CEO Duality and no significant negative effect on the Stock Return. Institutional ownership and no significant negative effect on the Stock Return. Size and Growth variable positive and significant impact on Stock Return. Board of Commissioners, the Audit Committee, the CEO of Duality, Institutional Ownership and Growth Size jointly significant effect on Stock Return. The result of determination coefficient of 10.2%, this suggests Stock Return 89.8% influenced by other variables outside the five variables of this study. Keywords: Return of Shares, the Board of Commissioners, the Audit Committee, the CEO of Duality, Institutional Ownership and Size Growth.